(untitled) (Research, Society and Development, 2021)
Objective: To describe and analyze the reported cases of severe varicella in Brazil and its social impact on public health. Methodology: This is a transversal observational descriptive study conducted with data collected by DATASUS, based on the survey of sociodemographic and clinical variables, from 2012 to 2019, and analyzed using prevalence calculations and the chi-square association test. Results: Of the 694,809 cases of severe varicella reported in Brazil, 2013 had the highest number of cases (28.51%), with a reduction in 2013 compared to 2019 (91.3%) and an increase of 55,36% from 2018 to 2019. Most cases were male, ranging from 51.15% to 52.31% (p <0.05), white (57.43%), school age group (34.1%) and the Southeast Region (31.47%). There was a clinical classification of the disease in 433,482 cases, most cured (99.8%; p <0.05). The preschool age group was the only one that presented, in 2019, a lower percentage of cases (11.58%) when compared to 2012 (30.35%). Conclusion: The introduction of the varicella vaccine resulted in a drop in the number of cases of the disease, with a socioeconomic impact on public health, and it is still necessary to demystify Fake News about the vaccine to improve vaccination coverage and prevent a new epidemic of the disease.